Research progress on return-to-work self-efficacy of young and middle-aged chronic disease patients (中青年慢性病患者重返工作自我效能的研究进展) - LEI Hong (雷宏); SUN Xinyu (孙新雨); YIN Anchun (尹安春) (中西医结合护理)
Return-to-work for young and middle-aged patients can not only resolve the patients' real life conflicts, but is also considered as an indication for recovery. In the process of return to work, the level of return-to-work self-efficacy is one of the factors that determine the progress of return to work, but there is a lack of uniformity in the research on return-to-work self-efficacy. A systematic and comprehensive discussion of the concepts, theoretical foundations, assessment tools, influencing factors, and intervention programs on return-to-work self-efficacy at home and abroad was conducted with the aim of providing a reference for clinical research. (重返工作不仅可以解决患者的现实冲突, 同时也被认为是康复的指征。重返工作自我效能的水平是决定重返工作进展的因素之一。本研究通过系统、全面的探讨国内外关于重返工作自我效能的概念、理论基础、测评工具、影响因素和干预方案, 以期为临床研究提供参考。)